Quantitative Viral Community DNA Analysis Reveals the Dominance of Single-Stranded DNA Viruses in Offshore Upper Bathyal Sediment from Tohoku, Japan - Yoshida, Mitsuhiro; Mochizuki, Tomohiro; Urayama, Syun-Ichi; Yoshida-Takashima, Yukari; Nishi, Shinro; Hirai, Miho; Nomaki, Hidetaka; Takaki, Yoshihiro; Nunoura, Takuro; Takai, Ken (Frontiers in Microbiology, 2018)
Previous studies on marine environmental virology have primarily focused on double-stranded DNA (dsDNA) viruses; however, it has recently been suggested that single-stranded DNA (ssDNA) viruses are more abundant in marine ecosystems. In this study, we performed a quantitative viral community DNA analysis to estimate the relative abundance and composition of both ssDNA and dsDNA viruses in offshore upper bathyal sediment from Tohoku, Japan (water depth = 500 m). The estimated dsDNA viral abundance ranged from 3 × 106 to 5 × 106 genome copies per cm3 sediment, showing values similar to the range of fluorescence-based direct virus counts. In contrast, the estimated ssDNA viral abundance ranged from 1 × 108 to 3 × 109 genome copies per cm3 sediment, thus providing an estimation that the ssDNA viral populations represent 96.3–99.8% of the benthic total DNA viromes. In the ssDNA virome, most of the identified viral sequences were associated with ssDNA viral families such as Circoviridae and Microviridae. The principle components analysis of the ssDNA viral sequence components from the sedimentary ssDNA virome libraries found that the different depth viral communities at the study site all exhibited similar profiles compared with deep-sea sediment ones at other reference sites. Our results suggested that deep-sea benthic ssDNA viruses have been significantly underestimated by conventional direct virus counts and that their contributions to deep-sea benthic microbial mortality and geochemical cycles should be further addressed by such a new quantitative approach.